The Influence of Islamic Studies Education on Professional Identity among Muslim University Graduates in the Southern Philippines - Hawla M. Upak; Saripa L. Talib; Rasul A. Gulo; Shahida M. Lintang (Indonesian Journal for Islamic Studies, 2026)
Background: Islamic Studies education plays a vital role in shaping the values, ethics, and professional conduct of Muslim graduates. While previous studies have focused on graduate employability and curriculum effectiveness, limited research has examined how Islamic Studies education contributes to the development of professional identity among Muslim university graduates in the Southern Philippines.Objectives: This study examined the influence of Islamic Studies education on the professional identity of Muslim graduates of Mindanao State University Maguindanao. Specifically, it assessed the relevance of Islamic knowledge in professional practice, identified challenges in aligning professional responsibilities with Islamic teachings, and explored curriculum enhancements that may strengthen professional identity formation.Methods: A quantitative-descriptive research design was employed involving 50 graduates of the Bachelor of Arts in Islamic Studies program of Mindanao State University–Maguindanao from 2020 to 2025. Data were collected through a structured survey questionnaire and analyzed using frequency, percentage, and weighted mean.Results: The results show that by encouraging accountability, honesty, moral behavior, and wise decision-making, Islamic Studies education greatly influenced graduates' professional identities. Despite obstacles including work obligations, a lack of institutional support, and time limits, participants thought Islamic knowledge was very relevant to workplace ethics and communication. They suggested career-oriented learning, ethics-focused training, and ongoing professional development.Conclusion: Islamic Studies education significantly contributes to the formation of professional identity among Muslim graduates by fostering ethical values, professional responsibility, and faith-based decision-making. Strengthening practical and career-oriented components of the curriculum may further enhance graduates’ professional development and workplace relevance.